SYNTHESIS AND ANTIOXIDATION OF AVOCADO (Persea Americana) LEAVES EXTRACT BY ABTS METHOD IN VITRO - Yustisia Dian Advistasari; Novi Elisa; Wulan Kartika Sari; Ainun Fawaid; Dhimas Adhityasmara; Claudius Hendraman B. Tobi (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Antioxidants play a role in inhibiting the development of metabolic syndrome, which is associated with several diseases. Increased free radical production can cause the body's system to require support from other antioxidants. The use of synthetic antioxidants is still limited due to their potential side effects. Natural antioxidants from natural ingredients, such as Avocado leaves, are needed. The purpose of this study was to determine compounds with antioxidant potential by testing the synthesis and bioequivalence of Avocado leaves extract in Vitro. The research methods used were Fourier Transform Infrared (FTIR) spectroscopy, Gas Chromatography-Mass Spectrometry (GC-MS), and ABTS assay. The results of the FTIR analysis of the Avocado leaves extract showed that the functional groups of organic compound molecules were N-H, H-C=O, C=C, C-O-H, and C-N. This result indicated that the Avocado extract contained phenolic compounds. GC-MS analysis result showed that the phytochemical components with the highest abundance in the Avocado leaves extract were the compounds at peak numbers 1 and 4, namely 9-Octadecenoic acid (Z)-, methyl ester (CAS) and 9-Octadecenoic acid (Z)-(CAS). Antioxidant test showed a linear regression equation of y = 0.267x + 35.007, R2 = 0.9491. This linear regression equation can be interpreted as a very strong and positive correlation. The IC50 value of Avocado leaves extract was 56.154, that categorized as a very strong antioxidant property. So it can be said that Avocado leaves extract has potential as an antioxidant.